Directed Action Verbs and their Semantic Features in the Uzbek Language - Buriyevna, Nashirova Dilnoza (Miasto Przyszłości, 2024)
Directed action verbs play a key role in the construction of narrative, descriptive, and pictorial texts. They provide dynamics and eventfulness of the presentation. Directed action verbs in the Uzbek language are a semantically and grammatically developed, functionally significant group of vocabulary. This article analyzes some semantic features of Directed action verbs in the Uzbek language.